2008
DOI: 10.1088/0256-307x/25/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Casimir Energy in Hartle–Hawking State

Abstract: We calculate the Casimir effect at finite temperature in Minkowski spacetime by using statistical method, the approximate expressions of the Casimir effect in the low and high temperature limits are also discussed. Then employing some general properties of the renormalized stress tensor, we obtain the Casimir energy stress tensor in Hartle-Hawking state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We have found that the integrand found in the tunneling method is always related to the entropy as ∂S ∂m dm [15]. This relation is not obvious from the tunneling picture alone, but with the connection to thermodynamics established the reason is just the one given by Hawking when he wrote down the same formula in 1976 [11].…”
Section: Some Consequences Of the Tunneling Formalismmentioning
confidence: 89%
“…We have found that the integrand found in the tunneling method is always related to the entropy as ∂S ∂m dm [15]. This relation is not obvious from the tunneling picture alone, but with the connection to thermodynamics established the reason is just the one given by Hawking when he wrote down the same formula in 1976 [11].…”
Section: Some Consequences Of the Tunneling Formalismmentioning
confidence: 89%
“…[3] In 2008, based on the phase shifts, Ref. [4] presented a quantum algorithm, which depicted the relation among the success probability, complexity, arbitrary phase shifts and the number of solutions.…”
Section: Introductionmentioning
confidence: 99%